Xanthine oxidase inhibitory study of eight structurally diverse phenolic compounds - Mehmood, Arshad; Li, Jiayi; Rehman, Ashfaq Ur; Kobun, Rovina; Llah, Inam U; Khan, Imran; Althobaiti, Fayez; Albogami, Sarah; Usman, Muhammad; Alharthi, Fahad; Soliman, Mohamed Mohamed; Yaqoob, Sanabil; et al. (Frontiers in Nutrition, 2022)
The present project was designed to explore the xanthine oxidase (XO) inhibitory mechanism of eight structurally diverse phenolic compounds (quercetin: C1, quercetin-3-rhamnoside: C2, 4, 5-O-dicaﬀeoylquinic acid: C3, 3, 5-O-dicaﬀeoylquinic acid: C4, 3, 4-O-di-caﬀeoylquinic acid: C5, 4-O-caﬀeoylquinic acid (C6), 3-O-caﬀeoylquinic acid: C7, and caﬀeic acid: C8). For this purpose, in-vitro and different computational methods were applied to determine the xanthine oxidase (XO) inhibitory potential of eight structurally diverse phenolic compounds. The results revealed that phenolic compounds (C1 to C8) possess strong to weak XO inhibitory activity. These results were further confirmed by atomic force microscopy (AFM) and 1HNMR analysis. Furthermore, computational study results revealed that phenolic compounds (C1 to C8) bind with the surrounding amino acids of XO at the molybdenum (MO) site. These in-vitro and in-silico results divulge that phenolic compounds have strong potential to lower uric acid levels via interacting with the XO enzyme and can be used to combat hyperuricemia.